Innate Immune Responses of Bat and Human Cells to Filoviruses: Commonalities and Distinctions - Kuzmin, Ivan V; Schwarz, Toni M; Ilinykh, Philipp A; Jordan, Ingo; Ksiazek, Thomas G; Sachidanandam, Ravi; Basler, Christopher F; Bukreyev, Alexander (Journal of virology, 2017)
Marburg (MARV) and Ebola (EBOV) viruses are zoonotic pathogens that cause severe hemorrhagic fever in humans. The natural reservoir of MARV is the Egyptian rousette bat ( ); that of EBOV is unknown but believed to be another bat species. The Egyptian rousette develops subclinical productive infection with MARV but is refractory to EBOV. Interaction of filoviruses with hosts is greatly affected by the viral interferon (IFN)-inhibiting domains (IID). Our study was aimed at characterization of innate immune responses to filoviruses and the role of filovirus IID in bat and human cells. The study demonstrated that EBOV and MARV replicate to similar levels in all tested cell lines, indicating that permissiveness for EBOV at cell and organism levels do not necessarily correlate. Filoviruses, particularly MARV, induced a potent innate immune response in rousette cells, which was generally stronger than that in human cells. Both EBOV VP35 and VP24 IID were found to suppress the innate immune response in rousette cells, but only VP35 IID appeared to promote virus replication. Along with IFN-α and IFN-β, IFN-γ was demonstrated to control filovirus infection in bat cells but not in human cells, suggesting host species specificity of the antiviral effect. The antiviral effects of bat IFNs appeared not to correlate with induction of IFN-stimulated genes 54 and 56, which were detected in human cells ectopically expressing bat IFN-α and IFN-β. As bat IFN-γ induced the type I IFN pathway, its antiviral effect is likely to be partially induced via cross talk. Bats serve as reservoirs for multiple emerging viruses, including filoviruses, henipaviruses, lyssaviruses, and zoonotic coronaviruses. Although there is no evidence for symptomatic disease caused by either Marburg or Ebola viruses in bats, spillover of these viruses into human populations causes deadly outbreaks. The reason for the lack of symptomatic disease in bats infected with filoviruses remains unknown. The outcome of a virus-host interaction depends on the ability of the host immune system to suppress viral replication and the ability of a virus to counteract the host defenses. Our study is a comparative analysis of the host innate immune response to either MARV or EBOV infection in bat and human cells and the role of viral interferon-inhibiting domains in the host innate immune responses. The data are useful for understanding the interactions of filoviruses with natural and accidental hosts and for identification of factors that influence filovirus evolution.